THE EFFECT OF RECIPROCAL TEACHING LEARNING MODEL INTEGRATED MIND MAP AND PERSISTENCE ON STUDENT RETENTION OF KINGDOM ANIMALIA CONCEPT - Dwi Septiana; Mieke Miarsyah; Ratna Komala (Universitas Negeri Jakarta, 2017)
The low score of students learning outcome on Kingdom Animalia concept indicate that there must an improvement of students retention. The aim of this study is to know the effect of reciprocal teaching learning model that integrated with mind map and persistence on students retention. The method that used in this research is quasi experiment with 2 x 2 factorial design. The instruments that used in this research are learning outcome test and persistence questionnaire. The subject of this study is students of X IPA 1 and 2 from SMAN 49 Jakarta totalling 72 students. Samples were taken using simple random sampling. Analysis of data used two way anova. The result showed that : 1) There is effect of reciprocal teaching learning model integrated mind map on students retention with p< 0,05, p = 0,03. 2). There is effect of persistence on students retention with p< 0,05, p = 0,00. 3) There is interaction between reciprocal teaching learning model integrated mind map and persistence on students retention with p< 0,05, p = 0,031.